Anti-freezing, anti-corrosion and anti-rust concrete as well as preparation method and application thereof

By using sulfur/silicon doped activated carbon in concrete, the problem of degradation of concrete corrosion and rust resistance after freeze-thaw cycle is solved, and the effect of significantly improving the anti-freeze and anti-corrosion and rust resistance of concrete is achieved.

CN119462022APending Publication Date: 2025-02-18BEIJING MUHU CONCRETE ADMIXTURE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411709420.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The anti-corrosion and rust resistance performance of concrete decreases after the freeze-thaw cycle, and the organic rust resistance agent is easily released into the environment after the freeze-thaw cycle, which reduces the overall performance of concrete.

Method used

Using sulfur/silica doped activated carbon, sulfur-containing polysilicon modifier is prepared by thiol-ene click reaction of vinyl cyclosiloxane and thiol silane coupling agent, and sulfur-containing polysilicon modifier is obtained by hydrolysis and alkali lignin cross-linking reaction. Silicon-modified alkali lignin microsphere precursor, and finally sulfur/silicon doped activated carbon is produced by carbonization and activation. This material has excellent adsorption properties for polar rust inhibitors, delaying their release and providing space for volume change for free water.

Benefits of technology

It significantly improves the corrosion-resistant rust resistance of concrete after freeze-thaw cycle, enhances its ability to resist extreme climates, and maximizes the service life of concrete engineering structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155288620000061
    Figure BDA0005155288620000061
Patent Text Reader

Abstract

The invention provides anti-freezing, anti-corrosion and anti-rust concrete as well as a preparation method and application thereof. The anti-freezing, anti-corrosion and anti-rust concrete is prepared from the following raw materials in parts by weight: 60 to 70 parts of cement, 30 to 40 parts of mineral admixture, 1 to 2 parts of sulfur / silicon doped activated carbon, 150 to 200 parts of quartz sand, 200 to 250 parts of pebbles, 1 to 1.5 parts of water reducing agent, 5 to 10 parts of anti-rust agent and 35 to 45 parts of water. The organic corrosion inhibitor is a compound of an organic amine salt, a thiourea derivative and a quaternary ammonium salt according to a mass ratio of (5-8): (3-5): (0.5-1), the mass sum of the cement and the mineral admixture is 100 parts, the sulfur / silicon doped activated carbon is firstly subjected to a sulfydryl-alkene click reaction through vinyl cyclosiloxane and a sulfydryl silane coupling agent to prepare a sulfur-containing multi-silicon modifier, then the sulfur-containing multi-silicon modifier is hydrolyzed, and the sulfur / silicon doped activated carbon is prepared. Performing cross-linking reaction on the hydrolysate and alkali lignin to obtain a sulfur-containing multi-silicon modified alkali lignin microsphere precursor; and finally carbonizing and activating the precursor to obtain the sulfur-containing multi-silicon modified alkali lignin microsphere.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete admixtures, and specifically relates to an antifreeze, anticorrosion and rust-resistant concrete anticorrosion and rust-resistant agent, a preparation method and an application thereof. Background Art

[0002] Reinforced concrete, as a structural material, has been widely used in engineering structures such as buildings, bridges, and tunnels. Saline soil, groundwater, and marine areas contain a variety of corrosive media, especially sulfates and chlorides, which corrode concrete structures and steel bars, causing great damage to reinforced concrete structures, reducing the durability of concrete structures, shortening the service life of engineering structures, and causing huge losses to the national economy. In order to meet the service life of engineering structures, composite anti-corrosion and rust-resistant admixtures that have high efficiency in reducing water, entraining air, increasing concrete density, and containing components that effectively prevent steel bar corrosion are generally used in concrete to extend the service life of engineering structures. For example, patent CN110981301B discloses an anti-corrosion and rust-resistant concrete and a preparation method thereof. The anti-corrosion and rust-resistant concrete includes the following components in parts by weight: 270-290 parts of cement, 60-70 parts of mineral powder, 70-90 parts of fly ash, 673-727 parts of sand, 950-970 parts of gravel, 111-165 parts of water, and 30-40 parts of admixture; the admixture includes a pumping agent and an anti-corrosion and rust inhibitor; the anti-corrosion and rust inhibitor includes the following components in parts by weight: 5-9 parts of modified epoxy resin, 1-5 parts of GWZB820 type reinforcing agent, 1.5-3.5 parts of eleostearic acid, 2.3-3.1 parts of 2BaO·SiO2, 3.2-4.8 parts of polyaluminum phosphate, 2.6-3.4 parts of water glass, 1.5-3.5 parts of sodium molybdate, and 1.8-2.6 parts of didecyldimethylammonium chloride. Patent CN109704675B discloses an anti-corrosion and rust-resistant concrete and its application, which includes the following components in parts by weight: 300-420 parts of cement, 680-730 parts of sand, 980-1200 parts of gravel, 35-50 parts of fly ash, 35-50 parts of mineral powder, 8-15 parts of pumping agent, 8-15 parts of concrete preservative, 8-15 parts of rust inhibitor and 150-200 parts of water. Patent CN113372066B discloses a high-durability concrete under high-salt service conditions and a preparation method thereof. The raw materials used for the concrete include the following components: cement, mineral powder, fly ash, expansion agent, fine aggregate, red brick powder, coarse aggregate, water reducer, air entraining agent, anticorrosion and rust inhibitor, water, highly absorbent resin, reinforcing fiber, epoxy resin microcapsules; the preparation method is: S1. first mix the red brick powder and water and let it stand; S2. mix and stir the cement, mineral powder, fly ash, water and water reducer, then add the remaining raw materials except the epoxy resin microcapsules and continue stirring, and finally add the epoxy resin microcapsules and continue stirring.

[0003] The above is a common application of using mineral admixtures and components to prevent steel corrosion to prevent corrosion and rust in concrete. While improving the density of concrete, it also synergizes with the rust-inhibiting function of organic rust-inhibiting components to improve the corrosion and rust-inhibiting performance of concrete. However, while mineral admixtures improve the density of concrete, they also reduce the volume change space of free water in the freezing cycle, resulting in enhanced connectivity of the capillary pores of concrete after the freezing cycle. Although it has no obvious effect on the overall mechanical strength of concrete, more organic rust inhibitors with high activity and strong penetration will be released into the environment after the freezing cycle, reducing the corrosion and rust-inhibiting performance of concrete. Therefore, it is necessary to improve concrete using mineral admixtures and organic rust inhibitors, improve its antifreeze performance, and further improve the corrosion and rust-inhibiting performance of concrete. Summary of the invention

[0004] In order to solve the problem of the decrease in the anti-corrosion and rust-proofing performance of concrete after the above-mentioned freeze-thaw cycle, the concrete provided by the present invention contains a sulfur / silicon doped activated carbon, which firstly prepares a sulfur-containing polysilicon modifier by a mercapto-ene click reaction of vinyl cyclosiloxane and mercaptosilane coupling agent, and then the sulfur-containing polysilicon modifier is hydrolyzed, and the hydrolysis product is cross-linked with alkali lignin to obtain a sulfur-containing polysilicon modified alkali lignin microsphere precursor, and finally the precursor is carbonized and activated. The prepared sulfur / silicon doped activated carbon has excellent adsorption performance for polar rust inhibitors, can delay the release of rust inhibitors, and also provide volume change space for free water, which can significantly improve the anti-corrosion and rust-proofing performance of concrete after freeze-thaw cycles without adversely affecting other properties of concrete.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A frost-resistant, anti-corrosion and rust-resistant concrete comprises the following raw materials in parts by weight: 60-70 parts of cement, 30-40 parts of mineral admixtures, 1-2 parts of sulfur / silicon-doped activated carbon, 150-200 parts of quartz sand, 200-250 parts of gravel, 1-1.5 parts of water reducer, 5-10 parts of rust inhibitor, and 35-45 parts of water; the organic rust inhibitor is a compound of organic amine salt, thiourea derivative, and quaternary ammonium salt in a mass ratio of 5-8:3-5:0.5-1, the mass sum of the cement and the mineral admixture is 100 parts, and the sulfur / silicon-doped activated carbon is prepared by a method comprising the following steps:

[0007] 1) dissolving vinyl cyclosiloxane and mercaptosilane coupling agent in an organic solvent, adding a photoinitiator and mixing evenly, irradiating with ultraviolet light under stirring conditions to react, and distilling under reduced pressure after the reaction to obtain a sulfur-containing polysilicon modifier for standby use;

[0008] 2) adding the sulfur-containing polysilicon modifier to an alcohol-water solution to carry out a hydrolysis reaction, adding an alkali lignin solution to carry out a cross-linking reaction after the hydrolysis reaction is completed, filtering, washing, and drying after the cross-linking reaction is completed to obtain a sulfur-containing polysilicon modified alkali lignin microsphere precursor for standby use;

[0009] 3) placing the sulfur-containing polysilicon-modified alkali lignin precursor in a calcining furnace and carbonizing it under an inert atmosphere, immersing the carbonized material in a zinc chloride solution, filtering, drying, activating it under an inert atmosphere, washing and grinding it after cooling, and obtaining sulfur / silicon-doped activated carbon.

[0010] In step 1), the vinyl cyclosiloxane derivative is selected from one or a combination of two or more of tetramethyltetravinylcyclotetrasiloxane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and pentamethylpentavinylcyclopentasiloxane. The mercaptosilane coupling agent is selected from one or a combination of two or more of mercaptopropyltrimethoxysilane and 2-mercaptoethyltriethoxysilane. The amount of vinyl cyclosiloxane and mercaptosilane coupling agent is such that the molar ratio of alkenyl to mercapto is 1-1.1:1-1.1, and the organic solvent is selected from one or a combination of two or more of dichloromethane, chloroform, acetone, and benzene. The photoinitiator is selected from one or a combination of two or more of diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxy-cyclohexyl ketone, and 2-hydroxy-2-methyl-phenylacetone-1. The amount of the photoinitiator is 1-2% of the sum of the molar amounts of the vinyl cyclosiloxane and the mercaptosilane coupling agent. The reaction time is 5 min-30 min. The illumination power density of the ultraviolet light is 400-500 mW / cm 2 .

[0011] In step 2), the alcohol in the alcohol-water solution is selected from one or a combination of two or more of methanol, ethanol, and isopropanol. The alcohol in the alcohol-water solution accounts for 90-95wt%. The mass ratio of the sulfur-containing polysilicon modifier to the alcohol-water solution is 2-2.5:100. The hydrolysis temperature is 40-60°C, and the hydrolysis reaction time is 0.5-1h. The weight average molecular weight of the alkali lignin is 1000-2000g / mol, and the alkali lignin is selected from one or a combination of two or more of wood pulp alkali lignin, wheat straw alkali lignin, bamboo pulp alkali lignin, and sugarcane bagasse alkali lignin. The alkali lignin solution is a mixed solution in which alkali lignin is dissolved in ethanol at a concentration of 10-20wt%. The mass ratio of the sulfur-containing polysilicon modifier to the alkali lignin is 20-25:100. The cross-linking reaction time is 12-24h. The washing is washing with water 1-3 times. The drying is drying at 60-100°C to constant weight.

[0012] In step 3), the carbonization temperature is 300-500°C, the carbonization time is 2-3h. The mass fraction of the zinc chloride solution is 30-50wt%, the mass ratio of the carbonized material to the zinc chloride solution is 1:1-3, the immersion time is 3-5h, and the drying is 60-100°C to constant weight. The activation temperature is 600-900°C, the activation time is 1-5h, and the mixture is washed with water until there is no Cl - Detection, drying at 100-120°C or natural drying, the grinding is grinding to an average particle size of 30-50 μm.

[0013] The organic amine salt is selected from one or a combination of two or more of dicyclohexylamine nitrite, cyclohexylamine carbonate, diisopropylamine nitrite, and diisobutylamine nitrite; the thiourea derivative is selected from one or a combination of two or more of allylthiourea, o-xylenethiourea, diethylthiourea, and 1,3-di-n-butylthiourea; and the quaternary ammonium salt includes one or a combination of two of mono-long-chain alkyl quaternary ammonium salt and di-long-chain alkyl quaternary ammonium salt.

[0014] The mono-long-chain alkyl quaternary ammonium salt is selected from one or a combination of two or more of dodecyltrimethylammonium chloride and tetradecyldimethylbenzylammonium chloride; the di-long-chain alkyl quaternary ammonium salt is selected from one or a combination of two or more of dioctyldimethylammonium chloride and didecyldimethylammonium chloride.

[0015] The cement is silicate cement with a strength of 42.5-52.5.

[0016] The mineral admixture is a mixture of mineral powder and fly ash in a mass ratio of 1-2:1-2.

[0017] The mineral powder is selected from one of S105 grade mineral powder, S95 grade mineral powder, S75 grade mineral powder, or a combination of two or more thereof.

[0018] The fly ash is selected from Class I fly ash.

[0019] The quartz sand grading comprises 60-70wt% of quartz sand with a fineness modulus of 2.2-2.5 and 30-40wt% of quartz sand with a fineness modulus of 2.5-3.

[0020] The stone is a continuously graded crushed stone of 5-25 mm.

[0021] The water reducing agent has a water reducing rate of 20-25%, and is selected from naphthalene-based water reducing agents and polycarboxylic acid-based water reducing agents, or a combination of the two.

[0022] The present invention also provides a method for preparing the above-mentioned antifreeze, anticorrosion and rust-resistant concrete, comprising the following steps: uniformly mixing cement, mineral admixtures, sulfur / silicon doped activated carbon, quartz sand, gravel, water reducer, rust inhibitor and water to obtain the antifreeze, anticorrosion and rust-resistant concrete.

[0023] The invention discloses an application of antifreeze, anticorrosion and antirust concrete in coastal and marine engineering concrete structures.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The concrete of the present invention comprises a sulfur / silicon doped activated carbon, which firstly prepares a sulfur-containing polysilicon modifier by a mercapto-ene click reaction with vinyl cyclosiloxane and a mercaptosilane coupling agent, then hydrolyzes the sulfur-containing polysilicon modifier, and cross-links the hydrolysis product with alkali lignin to obtain a sulfur-containing polysilicon modified alkali lignin microsphere precursor, and finally the precursor is carbonized and activated to obtain the sulfur / silicon doped activated carbon. The sulfur / silicon doped activated carbon has excellent adsorption performance for polar rust inhibitors, can delay the release of the rust inhibitors, and provides a volume change space for free water, can significantly improve the anti-corrosion and rust-resistant performance of concrete after freeze-thaw cycles, improve the ability of concrete to resist extreme climates, and extend the service life of concrete engineering structures to the maximum extent. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.

[0027] The alkali lignin is wood pulp alkali lignin with a weight average molecular weight of 1400 g / mol, purchased from Gaotang County Lixin Lignin Co., Ltd.

[0028] The crushed stone was purchased from Shandong Baotian Stone Industry Co., Ltd.: using a continuous gradation of 5-25mm.

[0029] Quartz sand was purchased from Zhongsha New Materials (Zhaoqing City) Co., Ltd.: 60wt% of quartz sand with a fineness modulus of 2.3 and 40wt% of quartz sand with a fineness modulus of 3.

[0030] SSF-1000 series naphthalene-based high-efficiency water-reducing agent has a water-reducing rate of 21.8% and was purchased from Hubei Shanshufeng Building Materials Technology Co., Ltd.

[0031] Coconut shell activated carbon powder was purchased from Gongyi Botao Water Purification Material Factory with an average particle size of 46 μm.

[0032] Example 1

[0033] 1) Dissolve 0.1 mol 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 0.3 mol mercaptopropyltrimethoxysilane in 100 mL dichloromethane, add 0.008 mol 2,2-dimethoxy-2-phenylacetophenone and mix well. Irradiate with ultraviolet light for 30 min under stirring conditions. The illumination power density is 500 mW / cm 2After the reaction is completed, the organic solvent is removed by distillation under reduced pressure to obtain a sulfur-containing polysilicon modifier for standby use;

[0034] 2) Add 25g of sulfur-containing polysilicon modifier to 1000g of alcohol-water solution prepared by ethanol and water in a mass ratio of 95:5, control the temperature at 60°C and stir at a low speed of 100r / min for hydrolysis reaction for 1h, after the hydrolysis reaction is completed, add 500g of 20wt% alkali lignin solution (solvent is ethanol) under high speed stirring of 500r / min for cross-linking reaction for 12h, filter after the cross-linking reaction, wash 3 times with ethanol and water alternately, and dry at 100°C to constant weight to obtain a sulfur-containing polysilicon modified alkali lignin microsphere precursor for standby use;

[0035] 3) 100 g of sulfur-containing polysilicon-modified alkali lignin precursor was placed in a calcining furnace and carbonized at 500 ° C for 2 h under a nitrogen atmosphere. The carbonized material was immersed in 200 g of a 40 wt% zinc chloride solution for 5 h, filtered, dried at 100 ° C to constant weight, activated at 800 ° C for 3 h in a nitrogen atmosphere, cooled, and washed with water until there was no Cl - Detect and grind to an average particle size of 50 μm to obtain sulfur / silicon doped activated carbon;

[0036] 4) Mix 600g of cement, 200g of S95 grade mineral powder, 200g of grade I fly ash, 20g of sulfur / silicon doped activated carbon, 1500g of quartz sand, 2100g of crushed stone, 15g of water reducer, 100g of rust inhibitor prepared by mixing dicyclohexylamine nitrite, o-xylene thiourea and dodecyltrimethylammonium chloride in a mass ratio of 8:3:1, and 420g of water to obtain frost-resistant, anti-corrosion and rust-resistant concrete.

[0037] Example 2

[0038] The rest is the same as Example 1, except that in step 4), the amount of sulfur / silicon doped activated carbon is 10 g.

[0039] Example 3

[0040] The rest is the same as Example 1, except that, in step 1), 0.1 mol of tetramethyltetravinylcyclotetrasiloxane and 0.4 mol of mercaptopropyltrimethoxysilane are dissolved in 110 mL of dichloromethane, 0.01 mol of 2,2-dimethoxy-2-phenylacetophenone is added and mixed evenly, and the mixture is reacted under ultraviolet light for 30 min under stirring conditions, and the illumination power density is 500 mW / cm 2 After the reaction is completed, the organic solvent is removed by distillation under reduced pressure to obtain a sulfur-containing polysilicon modifier for later use.

[0041] Example 4

[0042] The rest is the same as Example 1, except that in step 4), the amount of rust inhibitor used is 50 g.

[0043] Example 5

[0044] The rest is the same as Example 1, except that in step 4), an equal mass of dioctyldimethylammonium chloride is used to replace dodecyltrimethylammonium chloride.

[0045] Example 6

[0046] 1) Dissolve 0.1 mol 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and 0.3 mol mercaptopropyltrimethoxysilane in 100 mL dichloromethane, add 0.008 mol 2,2-dimethoxy-2-phenylacetophenone and mix well. Irradiate with ultraviolet light for 30 min under stirring conditions. The illumination power density is 500 mW / cm 2 After the reaction is completed, the organic solvent is removed by distillation under reduced pressure to obtain a sulfur-containing polysilicon modifier for standby use;

[0047] 2) Add 25g of sulfur-containing polysilicon modifier to 1000g of alcohol-water solution prepared by ethanol and water in a mass ratio of 90:10, control the temperature at 60°C and stir at a low speed of 300r / min for hydrolysis reaction for 1h, after the hydrolysis reaction is completed, add 500g of 20wt% alkali lignin solution (solvent is ethanol) under high speed stirring of 500r / min for cross-linking reaction for 12h, filter after the cross-linking reaction, wash 3 times with ethanol and water alternately, and dry at 100°C to constant weight to obtain a sulfur-containing polysilicon modified alkali lignin microsphere precursor for standby use;

[0048] 3) 100 g of sulfur-containing polysilicon-modified alkali lignin precursor was placed in a calcining furnace and carbonized at 500 ° C for 2 h under a nitrogen atmosphere. The carbonized material was immersed in 200 g of a 40 wt% zinc chloride solution for 5 h, filtered, dried at 100 ° C to constant weight, activated at 800 ° C for 3 h in a nitrogen atmosphere, cooled, and washed with water until there was no Cl - Detect and grind to an average particle size of 50 μm to obtain sulfur / silicon doped activated carbon;

[0049] 4) Mix 700g of cement, 100g of S95 grade mineral powder, 200g of grade I fly ash, 10g of sulfur / silicon doped activated carbon, 1500g of quartz sand, 2100g of crushed stone, 15g of water reducer, 100g of rust inhibitor prepared by mixing dicyclohexylamine nitrite, o-xylene thiourea and dodecyltrimethylammonium chloride in a mass ratio of 5:5:0.5, and 420g of water to obtain frost-resistant, anti-corrosion and rust-resistant concrete.

[0050] Comparative Example 1

[0051] Mix 600g of cement, 200g of S95 grade mineral powder, 200g of grade I fly ash, 20g of activated carbon powder, 1500g of quartz sand, 2100g of gravel, 15g of water reducer, 100g of rust inhibitor prepared by mixing dicyclohexylamine nitrite, o-xylene thiourea and dodecyltrimethylammonium chloride in a mass ratio of 8:3:1, and 420g of water to obtain frost-resistant, anti-corrosion and rust-resistant concrete.

[0052] The concrete prepared in the above examples and comparative examples was subjected to the following performance tests:

[0053] Compressive strength: Tested in accordance with GB / T 50081-2019 Test methods for physical and mechanical properties of concrete.

[0054] Electrochemical comprehensive test: refer to Appendix A2 of the technical specification for steel bar rust inhibitors in the standard YB / T9231-2009, where the mortar specimen is: cement + mineral admixture, rust inhibitor, standard sand, water, 1000g: 2000g: 500g of rust inhibitors in each embodiment or comparative example. The specimens are made according to the standard and cured to the specified age for electrochemical comprehensive test. The judgment standard is that the accelerated corrosion current measured at room temperature for 168h is less than 150μA, which is qualified.

[0055] Chloride ion diffusion performance: Tested in accordance with standard GB / T 50082-2009 Test method for long-term performance and durability of ordinary concrete.

[0056] Freezing resistance cycle test: the specimens cured to the specified age in the electrochemical comprehensive test are first tested with reference to the standard GB / T50082-2009 Test method for long-term performance and durability of ordinary concrete, and freeze-thaw cycles (quick freezing method) are carried out, -20℃ / 2h, 20℃ / 2h, repeated 250 times; after the freeze-thaw cycle, the electrochemical comprehensive test and compressive strength test are carried out again after heat treatment in an oven at 40℃ for 24h; and the compressive strength loss rate is calculated.

[0057] Table 1 Performance test results

[0058]

[0059] It can be seen from the performance test results of the embodiments and comparative examples that the concrete prepared by the present invention has excellent mechanical strength and resistance to chloride ion penetration. The sulfur / silicon doped activated carbon can improve the rust resistance of concrete without affecting the mechanical properties, significantly improve the rust resistance of concrete after freeze-thaw cycles, improve the ability of concrete to resist extreme climates, and maximize the service life of concrete engineering structures.

[0060] It can be seen from the highest current at 168h that the surface properties and dosage of sulfur / silicon doped activated carbon have a great influence on the rust inhibition performance of the rust inhibitor. It is speculated that the changes in surface properties and dosage are related to the controlled release of the rust inhibitor and the size of the expansion space provided during the free water freezing cycle, which in turn affects the rust inhibition performance.

[0061] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A frost-resistant, anti-corrosion and rust-resistant concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of cement, 30-40 parts of mineral admixture, 1-2 parts of sulfur / silicon doped activated carbon, 150-200 parts of quartz sand, 200-250 parts of stone, 1-1.5 parts of water reducer, 5-10 parts of rust inhibitor, and 35-45 parts of water; the organic rust inhibitor is a compound of organic amine salt, thiourea derivative, and quaternary ammonium salt in a mass ratio of 5-8:3-5:0.5-1, the mass sum of the cement and the mineral admixture is 100 parts, and the sulfur / silicon doped activated carbon is prepared by a method comprising the following steps: 1) dissolving vinyl cyclosiloxane and mercaptosilane coupling agent in an organic solvent, adding a photoinitiator and mixing evenly, irradiating with ultraviolet light under stirring conditions to react, and distilling under reduced pressure after the reaction to obtain a sulfur-containing polysilicon modifier for standby use; 2) adding the sulfur-containing polysilicon modifier to an alcohol-water solution to carry out a hydrolysis reaction, adding an alkali lignin solution to carry out a cross-linking reaction after the hydrolysis reaction is completed, filtering, washing, and drying after the cross-linking reaction is completed to obtain a sulfur-containing polysilicon modified alkali lignin microsphere precursor for standby use; 3) placing the sulfur-containing polysilicon-modified alkali lignin precursor in a calcining furnace and carbonizing it under an inert atmosphere, immersing the carbonized material in a zinc chloride solution, filtering, drying, activating it under an inert atmosphere, washing and grinding it after cooling, and obtaining sulfur / silicon-doped activated carbon.

2. The antifreeze, anticorrosion and rust-resistant concrete according to claim 1 is characterized in that: In step 1), the vinyl cyclosiloxane derivative is selected from one or a combination of two or more of tetramethyltetravinylcyclotetrasiloxane, 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and pentamethylpentavinylcyclopentasiloxane; the mercaptosilane coupling agent is selected from one or a combination of two or more of mercaptopropyltrimethoxysilane and 2-mercaptoethyltriethoxysilane.

3. The antifreeze, anticorrosion and rust-resistant concrete according to claim 1 is characterized in that: In step 1), the amounts of vinyl cyclosiloxane and mercaptosilane coupling agent are such that the molar ratio of vinyl group to mercapto group is 1-1.1:1-1.

1.

4. The antifreeze, anticorrosion and rust-resistant concrete according to claim 1, characterized in that: In step 2), the mass ratio of the sulfur-containing polysilicon modifier to the alcohol-water solution is 2-2.5:100; the alkali lignin solution is a mixed solution of 10-20wt% alkali lignin dissolved in ethanol; the mass ratio of the sulfur-containing polysilicon modifier to the alkali lignin is 20-25:

100.

5. The antifreeze, anticorrosion and rust-resistant concrete according to claim 1, characterized in that: In step 2), the weight average molecular weight of the alkali lignin is 1000-2000 g / mol, and the alkali lignin is selected from one or a combination of two or more of wood pulp alkali lignin, wheat straw alkali lignin, bamboo pulp alkali lignin, and sugarcane bagasse alkali lignin.

6. The antifreeze, anticorrosion and rust-resistant concrete according to claim 1, characterized in that: In step 3), the carbonization temperature is 300-500°C, the carbonization time is 2-3h, the mass fraction of the zinc chloride solution is 30-50wt%, the immersion mass ratio of the carbonized material to the zinc chloride solution is 1:1-3, the immersion time is 3-5h, the activation temperature is 600-900°C, and the activation time is 1-5h; the grinding is grinding to an average particle size of 30-50μm.

7. The antifreeze, anticorrosion and rust-resistant concrete according to claim 1, characterized in that: The organic amine salt is selected from one or a combination of two or more of dicyclohexylamine nitrite, cyclohexylamine carbonate, diisopropylamine nitrite, and diisobutylamine nitrite; the thiourea derivative is selected from one or a combination of two or more of allylthiourea, o-xylenethiourea, diethylthiourea, and 1,3-di-n-butylthiourea; and the quaternary ammonium salt includes one or a combination of two of mono-long-chain alkyl quaternary ammonium salt and di-long-chain alkyl quaternary ammonium salt.

8. The antifreeze, anticorrosion and rust-resistant concrete according to claim 1, characterized in that: The cement is silicate cement with a strength of 42.5-52.5; the mineral admixture is a mixture of mineral powder and fly ash in a mass ratio of 1-2:1-2; the mineral powder is selected from one or a combination of two or more of S105 grade mineral powder, S95 grade mineral powder, and S75 grade mineral powder; the fly ash is selected from Class I fly ash; the single-long-chain alkyl quaternary ammonium salt is selected from one or a combination of two or more of dodecyltrimethylammonium chloride and tetradecyldimethylbenzylammonium chloride; the double-long-chain alkyl quaternary ammonium salt is selected from one or a combination of two or more of dioctyldimethylammonium chloride and didecyldimethylammonium chloride.

9. The method for preparing the frost-resistant, corrosion-resistant and rust-resistant concrete according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: uniformly mixing cement, mineral admixture, sulfur / silicon doped activated carbon, quartz sand, gravel, water reducing agent, rust inhibitor and water to obtain antifreeze, anticorrosion and rust resistant concrete.

10. Application of the frost-resistant, anti-corrosion and rust-resistant concrete according to any one of claims 1 to 8 in coastal and marine concrete structures.

Citation Information

Patent Citations

  • A corrosion-resistant and rust-inhibiting concrete and its application

    CN109704675B

  • A high-durability concrete under high-salt service conditions and its preparation method

    CN113372066B